Uso da termografia para avaliação de manifestações patológicas em fachadas de edificações - Paula Martins Binoti (2023)
The facade plays an important role in the building, in addition to the aesthetic factor, this system is responsible for sealing the construction. Therefore, the emergence of pathological manifestations affects its performance, making the system vulnerable to water and gases infiltration, giving rise to the manifestation of construction. Thus, considering that the anomalies are progressive, tending to worsen over time, as well as that the repair becomes easier, cheaper and more effective the sooner the correction is made, it becomes desirable to identify the anomalies early. In this context, infrared thermography presents itself as a technique capable of assisting in monitoring the emergence of anomalies in buildings facades. At this point, this work aims to evaluate the thermography technique for the purpose of identifying pathological manifestations in facades of building under real conditions of use and contour. To achieve this, passive thermographic inspections and visual inspections were carried out on facades with different coatings. From the generated images, proceed with a qualitative analysis to identify anomalies and compare them with the results of the visual test. Furthermore, data was collected regarding the execution of inspections that allowed evaluating tha advantages and limitations of thermographic inspection. Finally, the potential of thermography in facade tests was verified. It was observed that the technique identified anomalies such as coating adhesion failure and early, hidden infiltrations, as well as identifying the magnitude of subsurface damage from visible anomalies. However, it was found to be a technique that requires training on the operator to identify existing adversities in the microclimate of the building, capable of generating wrong results. Additionally, it was identified that the technique can not be executed on some facades, mainly due to the viewing angle. However, it was concluded that the technique has more advantages than limitations. It was also shown to be a test with low safety risk, because it is generally done on the ground floor and/or in a safe place.